Ascertaining the concept of “Fluidity” in sexual and gender identity and orientation: a critical analysis of crossing and call me by your name - Alam, Samina (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2023.